2017
DOI: 10.4269/ajtmh.17-0048
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Risk of Cholera in Haiti following Hurricane Matthew

Abstract: Damage to the inferior and fragile water and sanitation infrastructure of Haiti after Hurricane Matthew has created an urgent public health emergency in terms of likelihood of cholera occurring in the human population. Using satellite-derived data on precipitation, gridded air temperature, and hurricane path and with information on water and sanitation (WASH) infrastructure, we tracked changing environmental conditions conducive for growth of pathogenic vibrios. Based on these data, we predicted and validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 23 publications
1
53
0
Order By: Relevance
“…Consequently, satellite precipitation estimates, often in NRT, are increasingly becoming the standard precipitation data source in these environments. The IMERG NRT data have been used to track environmental conditions on the ground in order to help predict and validate the risk of cholera infection, for example, as shown in Figure for Haiti immediately after Hurricane Matthew in October 2016 (Khan et al ., ). Studies using TRMM have shown that areas of wetter conditions in the higher elevations of Uganda are often associated with increased incidence of Black Plague (MacMillan et al ., ; Monaghan et al ., ).…”
Section: Applications Of Gpm Data For Societal Benefitmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, satellite precipitation estimates, often in NRT, are increasingly becoming the standard precipitation data source in these environments. The IMERG NRT data have been used to track environmental conditions on the ground in order to help predict and validate the risk of cholera infection, for example, as shown in Figure for Haiti immediately after Hurricane Matthew in October 2016 (Khan et al ., ). Studies using TRMM have shown that areas of wetter conditions in the higher elevations of Uganda are often associated with increased incidence of Black Plague (MacMillan et al ., ; Monaghan et al ., ).…”
Section: Applications Of Gpm Data For Societal Benefitmentioning
confidence: 99%
“…In terms of algorithm and products for extended operations, the mission seeks to address the following major topics: lengthen the temporal record by inter-calibrating datasets back to 1998 (for the complete TRMM record, Figure modified from Khan et al (2017) expected release in 2018), extend GPM merged constellation algorithms pole to pole and improve their morphing process, and improve the estimates of falling snow and light rainfall. One critical issue is to improve space-borne estimates of precipitation over orographic and other complex surface features.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Where there are shortages, modelling suggests even a single dose has demonstrable efficacy and may be important in outbreak control [15]. This high-coverage two-dose campaign likely contributed to preventing cholera cases in the aftermath of Hurricane Matthew, [16], however protection is unlikely to last beyond three years [17] and the effect of a six-month delay between doses is not known. Vaccine effectiveness remains to be estimated, and further studies will be important to fully evaluate this intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Cholera transmits via drinking water contaminated with Vibrio cholerae bacteria, which is the main causative agent of cholera (Bentivoglio and Pacini, 1995). For an epidemic cholera outbreak to occur in a region, broadly three criterions are required to be fulfilled: 1) presence of V. cholerae in waterbodies, the causative agent of cholera, near to high population settlement 2) triggering hydroclimatic condition for the growth and proliferation of vibrios, 3) a fragile or broken water and sanitation accessibility or in other words WASH infrastructure for the transmission of vibrios to human population (Khan et al, 2017. V. cholerae is known for its ability to cause pandemics, thereby it is considered as unique among the diarrheal pathogens (Austin, 2010 andFaruque et al, 2004).…”
Section: List Of Tablesmentioning
confidence: 99%
“…This study produces a R-JAVA based cholera forecasting software with user-friendly graphical user interface (GUI). The hydroclimatic risk assessment algorithm (Khan et al, 2017) is implemented and can be simulated using this software.…”
Section: Development Of Cholera Risk Forecasting Software (Khan Jutlamentioning
confidence: 99%